2012
DOI: 10.1002/ajmg.a.35484
|View full text |Cite
|
Sign up to set email alerts
|

Antibody deficiency in adults with 22q11.2 deletion syndrome

Abstract: There are limited data on immunological disorders, infection profile, and autoimmunity among adults with the 22q11.2 deletion syndrome (22q11.2DS) in the literature. To expand this knowledge base, we evaluated immunoglobulin levels, lymphocyte subsets, and T‐cell function in 26 adults, consecutively referred to our 22q11.2DS multidisciplinary team. Their medical records were also reviewed with respect to frequency and severity of infections and autoimmune disorders. Six patients had low immunoglobulin levels; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
2
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 28 publications
0
17
2
1
Order By: Relevance
“…Another contrast is the reported prevalence of immunoglobulin abnormalities in 22q11.2 deletion syndrome of 6% in recent studies 44,45 and 40% in older reports, 42,43 with the prevalence of 61% in our collected cohort. However, we only had information on immunoglobulin levels from 33 of 59 (56%) patients.…”
Section: Immunological Abnormalities Reported In Charge Syndromecontrasting
confidence: 97%
See 2 more Smart Citations
“…Another contrast is the reported prevalence of immunoglobulin abnormalities in 22q11.2 deletion syndrome of 6% in recent studies 44,45 and 40% in older reports, 42,43 with the prevalence of 61% in our collected cohort. However, we only had information on immunoglobulin levels from 33 of 59 (56%) patients.…”
Section: Immunological Abnormalities Reported In Charge Syndromecontrasting
confidence: 97%
“…Björk et al 45 found that 6 of 26 adult patients (23%) had low immunoglobulin levels. Autoimmune diseases, like rheumatoid diseases and idiopathic thrombocytopenia purpura, are seen in approximately 10% of patients with 22q11.2 deletion syndrome, 46 whereas no autoimmune diseases were seen in the CHARGE syndrome patients, although 3 of 59 (5%) patients with CHARGE syndrome had an Omenn-like syndrome, which has autoimmune-like features.…”
Section: Immunological Abnormalities Reported In Charge Syndromementioning
confidence: 99%
See 1 more Smart Citation
“…Data support a CD4 T cell count of >500 cells per µl as being the lower limit for safe vaccine administration 135,146,205–207 . A small percentage of patients will develop antibody deficiencies 208 , but the patient characteristics that predispose to this condition are not yet clear; periodic monitoring seems prudent. Patients with hypogammaglobulinaemia can be treated with immunoglobulin replacement.…”
Section: Managementmentioning
confidence: 99%
“…There have been several proposed mechanisms including altered regulatory T cell development in the face of limited thymic tissue, increased responses to self-antigens with homeostatic proliferation, and dysregulation due to lymphopenia (Di et al, 2015; Ferrando-Martinez et al, 2014; McLean-Tooke et al, 2007; Milner, Ward, Keane-Myers, & Paul, 2007; Sullivan, McDonald-McGinn, & Zackai, 2002; Tison et al, 2011). The most common autoimmune disease affecting 22q11.2 patients in childhood is idiopathic thrombocytopenic purpura, and the second most common in juvenile idiopathic arthritis (Bjork, Oskarsdottir, Andersson, & Friman, 2012; Gennery et al, 2002; McLean-Tooke et al, 2007). Platelet size and number are lower at baseline in most patients with the deletion, which may cause confusion with idiopathic thrombocytopenia purpura (Lawrence, McDonald-McGinn, Zackai, & Sullivan, 2003).…”
Section: Autoimmune Diseasementioning
confidence: 99%